(untitled) (Eurasian Journal of Philology Science and Education, 2026)
This article presents a comparative cultural-linguistic analysis of the representation of traditions and ritual discourse in Mukhtar Auezov’s epic novel The Path of Abai and selected plays by William Shakespeare (Hamlet, Romeo and Juliet, Macbeth, The Merchant of Venice, and Twelfth Night). The study explores how ritual language functions as a mechanism for encoding national worldview, social hierarchy, and moral values within Kazakh and English literary traditions. Drawing on ethnolinguistic analysis, speech act theory, discourse-pragmatic methodology, and cultural linguistics, the research examines 45 textual fragments that illustrate ritualized speech acts such as blessings, oaths, lamentations, curses, wedding formulas, and honor-related expressions. The findings demonstrate that ritual language in both corpora operates as a performative system that regulates social relations and legitimizes authority. In Auezov’s narrative, ritual discourse is grounded in oral-poetic tradition, ethnographic terminology, and communal forms of speech, reflecting collective cultural consciousness. In Shakespeare’s works, ritual language is shaped by liturgical, legal, and rhetorical conventions of the Elizabethan era, emphasizing institutional authority and individual moral responsibility. Despite cultural differences, both authors employ ritual speech as a structural and semantic device that transforms personal experience into socially validated action. The study contributes to contemporary cultural linguistics by proposing a comparative pragmatic framework for analyzing ritual discourse across civilizations. It demonstrates that literary language serves not only as an artistic medium but also as a repository of collective memory and a carrier of cultural identity. Keywords: ritual discourse, ethnolinguistics, cultural linguistics, performativity, Auezov, Shakespeare, national worldview, speech acts.